The treatment of closed finger and metacarpal fractures - Cavalcanti Kußmaul, Adrian; Kuehlein, Titus; Langer, Martin F.; Ayache, Ali; Unglaub, Frank (Deutsches Ärzteblatt, 2023)
Background: Fractures of the fingers and metacarpal bones are the most common fracture type in the upper limb, with an incidence of 114 to 1483 per 100 000 persons per year. The clinical importance of closed finger and metacarpal fractures is often underestimated; inadequate diagnostic and therapeutic measures may result in serious harm. This review concerns the basic elements of the diagnosis and treatment of finger and metacarpal fractures. Methods: This review of the incidence, diagnosis and treatment of finger and metacarpal fractures is based on pertinent publications retrieved by a selective search of the literature. Results: The main focus of treatment lies on restoration of hand function in consideration of the requirements of the individual patient. The currently available evidence provides little guidance to optimal treatment (level II evidence). Although most closed fractures can be managed conservatively, individualized surgical treatment is advisable in comminuted fractures and fractures with a relevant degree of torsional malposition, axis deviation, or shortening, as well as in intra-articular fractures. Minimally invasive techniques are, in principle, to be performed wherever possible, yet open surgery is sometimes needed because of fracture morphology. Postsurgical complication rates are in the range of 32–36%, with joint fusion accounting for 67–76% of the complications. 15% involve delayed fracture healing and pseudarthrosis. Conclusion: Individualized treatment for finger and metacarpal fractures can improve patients’ outcomes, with major socioeconomic and societal benefits. Further high-quality studies evaluating the relative merits of the available treatments are needed as a guide to optimized therapy.
Gesehen am 10.06.2024